2007
DOI: 10.1007/s12038-007-0120-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the human follicle-stimulating hormone-binding inhibitor and its N-terminal fragment on follicle-stimulating hormone-induced progesterone secretion by granulosa cells in vitro

Abstract: Intrafollicular factors play an important role in folliculogenesis. The follicle-stimulating hormone (FSH)-binding inhibitor (FSHBI), purified by our laboratory from human ovarian follicular fluid, has been shown to suppress ovulation and induce follicular atresia/apoptosis in mice as well as impair fertility in marmosets, the New World monkeys. The octapeptide, a peptide corresponding to the N-terminal region of human FSHBI (hFSHBI), has been synthesized and also shows FSHBI activity in vitro. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…However, in the OP-treated group, maximum apoptosis was observed in cumulus granulosa cells. This observation may corroborate our earlier findings that there is a drastic decrease in progesterone (P 4 ) secretion by granulosa cells when cultured in the presence of OP (Wadia et al 2007). Khamsi and Roberge (2001) reported that cumulus granulosa cells have the potential to secrete six times more progesterone compared with antral or basal granulosa cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in the OP-treated group, maximum apoptosis was observed in cumulus granulosa cells. This observation may corroborate our earlier findings that there is a drastic decrease in progesterone (P 4 ) secretion by granulosa cells when cultured in the presence of OP (Wadia et al 2007). Khamsi and Roberge (2001) reported that cumulus granulosa cells have the potential to secrete six times more progesterone compared with antral or basal granulosa cells.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, hGF 2 inhibited steroid production by granulosa cells (Wadia et al 2007), indicating an autocrine role of the peptide on granulosa cells of the follicles. Its ability to modulate ovarian function strengthens the need to understand its mechanism of action.…”
mentioning
confidence: 90%
“…However, it is likely that the differences in progesterone secretion would have been more pronounced after a longer perfusion period since this only partly involve the cAMP second messenger system. An additional method for evaluation of function and viability of ovarian tissue is ovarian cell culture with measurements of steroid secretion [45,46]. In the present study we cultured a mixture of all ovarian cell types, which is an established method to study ovarian function when cooperation between different cell types is needed [41].…”
Section: Discussionmentioning
confidence: 99%
“…This FRBI, as an FSH antagonist, blocks the binding of hFSH to rat granulosa cells. In vivo administration of FRBI caused the suppression of ovulation and induced follicular atresia in mice [7], further impaired fertility of marmosets at doses of 100µg/day and 300µg/day [9]. …”
Section: Introductionmentioning
confidence: 99%